IMPLEMENTATION OF DANCE EXTRACURRICULAR ACTIVITIES ON KINESTHETIC INTELLIGENCE OF UTUE STATE ELEMENTARY SCHOOL STUDENTS, PIDIE REGENCY - Maulina, Isnanda; Fitri, Aida; Mislinawati, Mislinawati (Universitas Syiah Kuala, 2025)
Extracurricular dance activities at SD Negeri Utue, Pidie Regency are attended by students from grades 3, 4 and 5. Judging from the total number of students in grades 3, 4 and 5, only a small number of students take part in extracurricular dance activities. Then students are often late in participating in activities, there are also students who don't pay attention and don't take the initiative to ask questions if they don't understand. This research aims to describe the implementation of dance extracurricular activities on students' kinesthetic intelligence at SD Negeri Utue, Pidie Regency. This research approach is a qualitative approach and descriptive research type. To obtain data, researchers used observation and interviews. Based on the results of data analysis, researchers obtained information that the implementation of dance extracurricular activities on students' kinesthetic intelligence at SD Negeri Utue, Pidie Regency is as follows: implementation of activities is carried out based on the aim of maintaining and increasing knowledge of dance through the activities carried out. A place for female students to develop and express themselves through dancing. Accommodating and accommodating female students who are talented in the art of dance. develop students' talents and interests, form a disciplined attitude, serve as a place to spend time for useful things. The conclusion of this research is that the implementation of dance extracurricular activities on the kinesthetic intelligence of students at SD Negeri Utue, Pidie Regency has mostly been carried out well as demonstrated by implementing several goals, functions, student participation in taking part in activities as well as coaching through the provision of materials, guidance, exercises, Even though there is still a lack of infrastructure for activities, students are interested and involved in the extracurricular dance activities that are carried out.